ACCOUNTING STUDENT LEADERSHIP BEHAVIOR: A DILEMMA FOR HIGHER EDUCATION - Yusep Mulyana; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2019)
The position and role of accountants in organizations are not related to decision-making positions and for this reason accounting students do not identify themselves as leaders in their future careers. Motivated by these assumptions, this study aims to determine the relationship between curriculum and ethics on career choices of accounting students and to find out the relationship between curriculum and decision making processes on accounting student leadership behavior. The samples used in the study were 70 respondents from STIESA accounting students and KUIS accounting students. Analysis of the data in this study uses correlation analysis with the help of SPSS version 22. The results of the analysis show that the relationship between curriculum and career choices in STIESA is negative, in QUIZ is positive and when combined STIESA and QUIZ the relationship that occurs is positive. The relationship that occurs between ethics and career choices in STIESA, QUIZ and in general when the analysis is combined is positive. While the relationship between curriculum and leadership behavior at STIESA is negative, the QUI is positive and the combination of STIESA and QUI is positive. Then the relationship that occurs between the decision making process and leadership behavior in STIESA, QUIZ and in general when the analysis is combined between STIESA students and QUI students is positive.